Validation of an operational advanced Gaussian model with the Copenhagen and Kincaid datasets. (4th August 2014) - Rizza, U.; Mangia, C.; Tirabassi, T.
A practical model for evaluating ground–level concentrations from elevated sources that applies a new Gaussian formulation for transport and vertical diffusion is presented. In the Gaussian formula, the source height is replaced by a virtual source height, which is expressed by simple functions of the vertical profiles of wind and turbulent diffusivity. The performances of the model are evaluated by comparing different lateral diffusion parameterisations.